Pengaruh Efisiensi Rasio, Ukuran Perusahaan dan Rasio Pasar terhadap Audit Report Lag pada Perusahaan Tambang yang Terdaftar di BEI Tahun 2020-2024 - Yanto, Farhan Dzaki Dwiki; Riswandi, Pedi; Seventeen, Winny Lian (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
Audit report lag, the time gap between the fiscal year-end and the release of an audited financial report, serves as a key measure of financial reporting timeliness. In the mining sector, where operational and regulatory complexities are high, delayed audit reporting can undermine transparency and investor trust. This study aims to analyze the influence of efficiency ratio, firm size, and market ratio on audit report lag among mining companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. Using a quantitative associative method, the study collects secondary data from annual reports of nine purposively selected mining firms. The analysis employs multiple linear regression along with classical assumption tests, including normality, multicollinearity, and heteroskedasticity. Findings show that none of the independent variabels efficiency ratio, firm size, or market ratio has a statistically significant impact on audit report lag, either partially or simultaneously. This result indicates that financial ratio-based metrics may not adequately explain audit delays in this sector. The research underscores the potential role of non-financial factors such as auditor workload, geographic dispersion, or internal controls in influencing audit timeliness. Future studies are encouraged to explore these additional variables to provide more holistic insights into audit report lag determinants.